Оценка экономических, экологических и прочностных показателей быстроходного дизеля - Авраменко, А. Н. (НТУ "ХПИ", 2009)
В роботі наводяться результати числового моделювання робочого циклу тракторного дизеля. Проводиться порівняльна оцінка економічних, екологічних показників дизеля та аналіз теплонапруженого стану головки циліндра при роботі дизеля на номінальному режимі. Для вирішення зв'язаної газодинамічної та термоструктурної задачі використовується програмний комплекс, оснований на методі скінчених елементів.

In work results of numerical settlement-experimental modeling of a nominal cycle of an tractor diesel engine are resulted. The comparative estimation of ecological parameters of a diesel engine and the settlement-experimental analysis of a heat-stressed condition of the head of the cylinder is carried out at work of a diesel engine on an operational mode. For the decision connected gasodynamics and thermostructural problems the program complex based on a method of final elements.
Keywords: вычислительная гидродинамика; камера сгорания; остаточные газы; впрыск топлива